(untitled) (International Journal of Environmental Sciences, 2025)
Background: Genetic disorders are an important health problem in Saudi Arabia. One main reason is the high rate of consanguinity, because many marriages happen between relatives. This increases the chance of inherited diseases in children and also adds pressure on the health system. In recent years, next-generation sequencing (NGS) became a useful tool for molecular diagnosis. It can detect many genetic mutations at the same time with speed and accuracy. However, there is still not enough data from local tertiary hospitals in Saudi Arabia. More studies are needed to understand the prevalence, types, and outcomes of genetic disorders. Such information can help in better health planning, early diagnosis, and improving patient care. Objective: This study aims to evaluate the diagnostic yield of next-generation sequencing (NGS) in a tertiary hospital in Saudi Arabia and to examine its effect on patient management. Methods: This was a retrospective and prospective study on 312 patients suspected with hereditary disorders between January 2023 and September 2025 in a Saudi tertiary hospital. Patients received targeted gene panels, clinical exome sequencing, or whole exome sequencing. Variants were classified by ACMG guidelines. The main outcomes were diagnostic yield, variant distribution, and clinical impact. Results: The total diagnostic yield was 38.1% (95% CI: 33.0–43.4%). Neurological disorders had the highest diagnostic rate (45.6%), followed by metabolic disorders (40.3%). Oncology cases showed the lowest rate (21.9%). In total, 162 variants were found. Of these, 119 were pathogenic or likely pathogenic, and 33 were variants of uncertain significance. Clinical management was changed in 22.8% of patients, especially through targeted therapies, avoiding unnecessary procedures, and reproductive counseling. Conclusion: NGS has high diagnostic yield and clinical impact in a Saudi tertiary hospital, mainly in neurological and metabolic disorders. These results support NGS as a first-line diagnostic tool and also show the importance of creating genomic databases for the Saudi population.